Rapid Progression After 177Lu-DOTATATE in Patients With Neuroendocrine Tumors. Issue 6 (July 2021) - Assi, Hussein A.; Hornbacker, Kathleen; Shaheen, Shagufta; Wittenberg, Theresa; Silberman, Robyn; Kunz, Pamela L.
Abstract : Abstract: Peptide receptor radionuclide therapy (PRRT) is a treatment option for somatostatin receptor–positive, unresectable or metastatic neuroendocrine tumors (NETs). Despite high disease control rates seen with PRRT, a subset of the NET population seems to have a short progression-free interval. We hypothesize that patients with NETs with rapid progression post-PRRT may have mixed low- and high-grade cell populations, and PRRT treats the lower-grade component, allowing the more aggressive high-grade component to progress. We report 7 patients with biopsy-proven NET who received PRRT with 177 Lu-DOTATATE at the Stanford Cancer Center who had evidence of progressive disease (PD) on or within 6 months of therapy. All patients had primary pancreatic, metastatic, well-differentiated NET on diagnosis and were heavily pretreated before receiving PRRT. Two patients had PD while on PRRT; 5 had PD within 6 months of completing PRRT. The median time from the last cycle to PD was 3.2 months (range, 1.1–4.6 months). The median progression-free survival was 7.7 months (95% confidence interval, 5.7–9.8 months). Three patients had a repeat biopsy post-PRRT, 2 of which demonstrated higher disease grade compared with their initial pathology. Further evaluation in larger patient cohorts is warranted to elucidate predictive factors of PRRT response/nonresponse to enable better patient selection.